Development Of Bismuth Nanoparticles For Lead And Cadmium Sensors Application - Teh, Jin Jian (Universiti Sains Malaysia, 2017)
In this study, bismuth nanoparticles (BiNPs) were synthesized using the hydrothermal method and deposited on Indium Tin Oxide (ITO) electrodes to modify the electrodes. Several synthesis parameters were studied: the effect of hydrothermal reaction period, the effect of volume of hydrazine hydrate and the effect of reaction temperature. The properties of BiNPs were then characterized using X-ray Diffractometer (XRD), Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). XRD analysis proved that pure bismuth with Rhombohedral structure of R-3m space group (ICDD Reference Code: 98-002-1658) was obtained for all samples. The synthesized BiNPs powders were in the size range of 73.0 nm to 150.0 nm with varying hydrothermal synthesis parameters. The synthesized BiNPs were then drop-casted on ITO electrodes, air dried and subjected to cyclic voltammetry (CV) and differential pulse anodic stripping voltammetry (DPASV) analyses. The BiNPs/ITO modified electrodes showed good performance in terms of detecting heavy metals with limit of detection of 2.5 μg/L for Pb(II). Besides, with 0.1 wt.% of Nafion solution, the BiNPs/ITO electrode was successfully applied for simultaneous detection of Pb(II) and Cd(II) for the interference studies. Finally, the BiNPs/ITO electrode was successfully applied to the practical use for the determination of Pb(II) in seawater sample. The results showed that BiNPs modified electrodes can be used for heavy metals sensors.